2003
DOI: 10.1152/japplphysiol.00208.2003
|View full text |Cite
|
Sign up to set email alerts
|

Compositional changes in lipid microdomains of air-blood barrier plasma membranes in pulmonary interstitial edema

Abstract: We evaluated in anesthetized rabbits the compositional changes of plasmalemmal lipid microdomains from lung tissue samples after inducing pulmonary interstitial edema (0.5 ml/kg for 3 h, leading to approximately 5% increase in extravascular water). Lipid microdomains (lipid rafts and caveolae) were present in the detergent-resistant fraction (DRF) obtained after discontinuous sucrose density gradient. DRF was enriched in caveolin-1, flotillin, aquaporin-1, GM1, cholesterol, sphingomyelin, and phosphatidylserin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 38 publications
1
38
1
Order By: Relevance
“…These results are supported by the report that AQP5 was detected in the Rab4-containing intracellular membrane fraction located in the subapical region of rat parotid glands (21). Although it was reported that AQP5 is not located in lipid rafts of lung (22), AQP1 is located in a particular subtype of lipid rafts called caveolae, which are plasmalemmal vesicles in lung (23) and Fig. 1.…”
Section: Aqp5 Located In Lipid Rafts Was Translocated To the Apical Psupporting
confidence: 80%
“…These results are supported by the report that AQP5 was detected in the Rab4-containing intracellular membrane fraction located in the subapical region of rat parotid glands (21). Although it was reported that AQP5 is not located in lipid rafts of lung (22), AQP1 is located in a particular subtype of lipid rafts called caveolae, which are plasmalemmal vesicles in lung (23) and Fig. 1.…”
Section: Aqp5 Located In Lipid Rafts Was Translocated To the Apical Psupporting
confidence: 80%
“…As mentioned above, the Brown and Rose method or its modiˆcations have been applied not only to cultured cells but also to various tissues, including chicken gizzard smooth muscle (64), mouse (67), rat and human (93,146) cerebral cortex, mouse (66,(147)(148)(149)(150)(151), rat (21,65,(152)(153)(154) and human (155) brain, rat cerebellum (152), bovine and mouse brain myelin (71,75,149,156), rat (157) and mouse (92) brain synaptosomes, rat (158), mouse (148) and rainbow trout (159) liver, rat (160), rabbit (161) and mouse (148) lung, rat lung endothelium (162), pig (67,70) and mouse kidney (148). However, additional care is necessary to evaluate the results obtained analyzing DRM prepared from tissues.…”
Section: H Drm From Tissuesmentioning
confidence: 99%
“…For example, T-cadherin is reported as a caveolae-associated protein in one study and as a lipid raft-associated protein in another study [37,38]. Aquaporin-1, Thy-1, IGF-1 receptor and N-cadherin, which are reported to co-fractionate with caveolin-1 [5,20,[21][22][23][24][25], are actually noncaveolar lipid microdomain-associated proteins ( Figure 2D). Thus, this modified sucrose density gradient provides a better technique with which to study caveolae.…”
Section: Discussionmentioning
confidence: 99%
“…Many lipid microdomain-associated proteins, such as Thy-1 (GPI-AP, glycosylphosphatidylinositol-anchored protein) [21], N-cadherin (membrane glycoprotein) [22,23], aquaporin-1 (membrane [24,25], IGF-1 receptor (membrane tyrosine kinase receptor) [5,20] and c-Yes (inner-membrane lipid-tethered protein) [18], were actually associated with noncaveolar lipid microdomains ( Figure 2D). Flotillin-1, a structural protein in membrane lipid microdomains [19], was associated with caveolae ( Figure 2D).…”
Section: Separation Of Caveolae and Noncaveolar Lipid Microdomainsmentioning
confidence: 99%